Financial Behavior of Gen Z and Millennial Shopee PayLater Users: A Digital Financial Literacy Perspective - Rizky Ardiyanto; Heni Susilowati (STIE Amkop Makassar, 2026)
The development of financial services through digital platforms (Fintech) has triggered a shift in public perception of digital credit. The use of the buy now pay later (BNPL) system, which is not accompanied by adequate financial literacy, is the background of this study. The focus of the study is to evaluate the impact of digital financial literacy, financial attitudes, and accounting literacy on the financial behavior of Shopee PayLater users in Semarang Regency. A quantitative approach was used in this study, with data obtained from distributing questionnaires to 53 Generation Z and millennial respondents through a purposive sampling technique. Furthermore, the data were analyzed using multiple linear regression. The results revealed that digital financial literacy and accounting understanding contribute significantly to financial behavior. Conversely, financial attitudes do not have a significant partial effect on financial behavior. Simultaneously, digital financial literacy, financial attitudes, and accounting literacy have a significant effect on financial behavior, with an Adjusted R² value of 0.456. These results indicate that the ability to understand digital finance and accounting insight is crucial in creating smarter and more organized financial behavior when using digital credit services. This research contributes to the development of financial behavior literature and education for PayLater users in managing financial responsibility more optimally.